London voices, London lives tales from a working capital - Hall, Peter 1932-2014 (Policy Press, 2007)
London Voices, London Lives addresses a question of great current importance for urban policy: what kind of a place is London in the twenty-first century, and how does it differ significantly from other parts of urban Britain? It addresses these questions in a unique way: over one hundred ordinary Londoners provide their answers in their own voices